Pengaruh Beauty Influencer dan Online Customer Review terhadap Keputusan Pembelian Produk Skincare Avoskin melalui Kepercayaan Konsumen - Mutiara Lestari; Budhi Cahyono (Lembaga Yasin AlSys, 2026)
The high level of competition in the skincare industry on e-commerce platforms, particularly TikTok Shop, requires digital marketing strategies capable of encouraging consumer purchase decisions. In this context, beauty influencers and online customer reviews are assumed to play an important role in shaping consumer trust, which affects purchase decisions for Avoskin skincare products. This study aimed to analyze the influence of beauty influencers and online customer reviews on purchase decisions for Avoskin skincare products through consumer trust. This study used a quantitative approach with a causal design. The research population consisted of TikTok Shop users in Semarang City with an unknown total population, while a sample of 100 respondents was determined using purposive sampling. Data were collected using an online questionnaire and analyzed through multiple linear regression with the assistance of SPSS. The results showed that beauty influencers and online customer reviews had a positive and significant effect on both consumer trust and purchase decisions. However, consumer trust had a positive but insignificant effect on purchase decisions. Thus, marketing strategies through beauty influencers and consumer reviews proved effective in increasing purchase decisions for Avoskin skincare products, although the role of consumer trust as a mediating variable was not yet optimal.